Post-war children in the perspective of william blake’s poems - Sivapalan, C.C.A.; Parameswaran, S. (University of Jaffna, 2012)
The poet and artist William Blake is described as a man of genius who devoted his entire life and imagination to express his bold original ideas. His poems in “Songs of Innocence” and “Songs of Experience” explore the real nature of the poor people during the Industrial Revolution in England. Even though his poems deal with a range of topical issues of poverty, child labour, political and social revolution, industrial revolution, and the church, they specifically focus on child abuse. Through these poems Blake perceives about the abuse of children in the eighteenth century England. While reading Blake’s poems, from Songs of Innocence and Songs of Experience the inner sufferings of affected children of post war Jaffna District seems to surface. During the conflict in Sri Lanka many children were orphaned, disabled, and abused. The statistical report of the District Child Development Committee of the Jaffna District Secretariat can be interpreted into Blake’s poems. This will lead to the conclusion that child abuse is as vibrant in the post war Jaffna as it was in Blake’s contemporary society of the industrial revolution era.
Keywords: Poverty; Child abuse; Statistical report; Inner sufferings